En folklorist ser på studiet av køn - Lützen, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
Sexuality is considered to be a social construction, ie. a phenomenon instilled with meaning by the particular culture within whose context it manifests itself. In other words, sexuality is not an immutable essence within the individual, but rather something existing in society. The present article presents an alternative interpretation of why certain women arrange their lives around a lesbian identity. As a rule, such divergent ways of life are considered as having an individual explanation; however, the ethnological researcher can provide a more analytical explanation of such cultural phenomena.